2017
DOI: 10.1088/1361-6528/aa5252
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nucleation of catalyst-free InAs nanowires on silicon

Abstract: Abstract. We report on the heterogeneous nucleation of catalyst-free InAs nanowires on Si (111) substrates by chemical beam epitaxy. We show that nanowire nucleation is enhanced by sputtering the silicon substrate with energetic particles. We argue that particle bombardment introduces lattice defects on the silicon surface that serve as preferential nucleation sites. The formation of these nucleation sites can be controlled by the sputtering parameters, allowing the control of nanowire density in a wide range.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The axial growth rate decreased to 42 µm/h at a higher temperature of 715 °C. Similar dependence of the axial growth rate of InAs NWs with the growth temperature was observed by MBE and MOVPE 24,34 where growth was governed by the thermally-activated adatom diffusion on the surface of the substrate and NW sidewalls. 20,34 HVPE growth is mainly driven by the balance between adsorption and desorption of precursor materials, and the kinetics of the dechlorination step.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The axial growth rate decreased to 42 µm/h at a higher temperature of 715 °C. Similar dependence of the axial growth rate of InAs NWs with the growth temperature was observed by MBE and MOVPE 24,34 where growth was governed by the thermally-activated adatom diffusion on the surface of the substrate and NW sidewalls. 20,34 HVPE growth is mainly driven by the balance between adsorption and desorption of precursor materials, and the kinetics of the dechlorination step.…”
Section: Resultssupporting
confidence: 70%
“…NWs grown by MOVPE generally exhibit higher growth rate due to higher material input and growth temperature compared to MBE. 22,23 However, for both techniques the authors show that vapor-solid (VS) growth of InAs NWs is mainly limited by surface diffusion of adatoms [23][24][25] , also exhibiting a high density of twin planes and stacking faults. 11,22,26 Hydride vapor phase epitaxy (HVPE) has shown exceptional results for both Au-catalysed and self-catalysed ultra-long GaAs NWs in terms of growth rate and crystalline quality without any polytypism regardless of NW diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Catalyst-free methods are instead not mediated by any metal or intermediate phase, but rather employ crystal growth rate anisotropies to drive the preferential growth in one dimension [ 5 ]. This technique, often referred to as vapor-solid, has been demonstrated for the growth of Si nanowires [ 113 ], III-V semiconductor [ 109 , 114 , 115 ], and ZnO nanowires [ 116 ]. Catalyst-free growth can be performed, exploiting a self-assembled growth approach which typically relies on substrate-nanowire lattice mismatch, or exploiting a selective area approach, such as selective area growth (SAG) or selective area epitaxy (SAE).…”
Section: Bottom-up Approaches To the Realization Of Ordered Arrays Of Vertically Aligned Semiconductor Nanowiresmentioning
confidence: 99%
“…In MBE and CBE, several groups showed that VS growth of InAs NWs was mainly limited by the surface diffusion of adatoms, which does not favor a pure crystalline quality of NWs that exhibit a high density of twin planes, stacking faults and alternating ZB/WZ segments along the growth axis [143,144,151]. MOVPE provided also very promising results in the case of SAG, even though the wires did not exhibit a pure crystalline quality all along the NWs length limited to few microns [152,153].…”
Section: Growth Of Inas Nws On Simentioning
confidence: 99%